Impact of Agricultural Non-Point Source Pollution on River Water Quality: Evidence From China - Xu, Hanxiao; Tan, Xinxiang; Liang, Jie; Cui, Yuhu; Gao, Qiang (Frontiers in Ecology and Evolution, 2022)
Identifying the effect of agricultural non-point source pollutants on water quality is very important for water pollution management. This study used NH3N as an indicator to empirically study the influence of fertilizer application on river water quality based on panel data of 46 prefecture-level cities and 18 state-controlled water quality monitoring points through which the main streams of Yangtze River and Yellow River flow from 2004 to 2019. It is found that: (1) An increase in agricultural fertilizer application amount will exacerbate water pollution, and the worsening water quality in the upper watershed and the influence of precipitation will lead to transboundary water pollution in the lower watershed. (2) The amount of fertilizer application and fertilizer application intensity had a threshold effect on river water quality pollution. When the former exceeded the threshold value of 11.496 tons, and the latter exceeded the threshold value of 7.991 ton/km2, the positive effect of fertilizer application on pollutants in rivers was further enhanced. (3) The amount of fertilizer applied had a long-term effect on water quality through a lagged effect, and as the number of lags increased, the accumulative effect of the negative influence gradually rose. Based on the findings of the empirical study, it is proposed that the inter-basin and inter-regional synergy should be formed in the prevention and control of agricultural non-point source pollution, and the overall top-level design of agricultural subsidies and agricultural environmental policies in the areas along the basin should be considered.